Flowers and greenscapes are nature's message to rejoice - Singh, Alka; Ahlawat, T R (Indian Horticulture, 2019)
The colorful and fragrant flowers have been integral part of our traditional and religious ceremonies and rituals for the hidden reasons which are now being revealed with science. Flowers stimulate and evoke a positive response in human beings either as pleasure or happiness that predict spring arrival often associated with prosperity. Viewing flowers or having plants at home or office may provide ample involuntary attention, increase positive feelings, block or reduce worrisome thoughts and promote restoration from stress as revealed from different scientific studies. Sensory elements of flowers like fragrance, colour, texture, softness, freshness, etc influence human psyche in different manners. Specific floral scents influence neurological responding in human psyche. There is a significant influence of flowers on human psyche and emotions, which directly induces happiness and good health and thereby influences positive outlook, work culture and performance.